Vascular reconstitution in the tumor for more effective tumor immunotherapy. Issue 4 (3rd March 2021) - Takakura, Nobuyuki
Abstract: It has been widely accepted that the regulation of the tumor microenvironment is an important strategy in cancer treatment. Particularly, control of the tumor vasculature has been suggested to be critical for antitumor immunotherapy. Effectiveness of cancer immunotherapy depends on the quality and quantity of immune cells infiltrating into tumor tissues, which may be affected by the status of the tumor vasculature. Under physiological conditions, immune cells migrate from the intravascular lumen into the parenchyma especially by passing through the vascular wall of venulae. Extravasation of immune cells is induced from venulae where endothelial cells (ECs) are fully covered with pericytes from the basal side. Interaction of pericytes with ECs contributes to immune cell extravasation by several steps, ie, adhesion of immune cells to intraluminal ECs, transmigration, and chemotaxis of immune cells. Blood vessels are structurally immature and non‐functional in tumors, and therefore, induction of maturation in the tumor vasculature is a promising strategy for effective cancer therapies and is relevant not only for immune cell migration but also drug delivery. Abstract : It has been widely accepted that the regulation of the tumor microenvironment is an important strategy in cancer treatment. Control of the tumor vasculature has been suggested to be critical for antitumor immunotherapy. Effectiveness of cancer immunotherapy depends on the quality and quantity of immune cells infiltrating into tumor tissues, possibly affected by the status of the tumor vasculature.